The Old Town of Ampenan, from cultural heritage towards economic empowerment / Nurhikmah, S.I.P., M. Hum - M.Hum, Nurhikmah (2019)
One of the most important and historical spot in West Nusa Tenggara is Ampenan. This is a particular city that known as Old Town, located in the city of Mataram, Lombok Island. Many cities in Indonesia has to be Old Town, for example Jakarta and Semarang. Ampenan has high historical value, a symbol of multiculturalism, and since 2016, has been used as a national heritage by UNESCO. Formerly, this region as the largest city center and trade in West Nusa Tenggara. Various art deco buildings tell of the glory of Ampenan in the past.